Consumption of Alcohol and Psychosocial Determinants among Students of Medicine and Medical Technology - Maria Josefa Arcaya Moncada (SMAD, Revista Electrónica en Salud Mental, Alcohol y Drogas, 2019)
The objective was to evaluate alcohol consumption and its association with psychosocial determinants among students of medicine and medical technology at the Faculty of Medicine, in the Universidad Nacional Mayor de San Marcos, Peru. This cross-sectional study was designed with 219 students. The Alcohol Use Disorder Identification Test and psychosocial determinants were used. The prevalence of alcohol use in the last year was 69.5%, with predominance of use by male (71.6%) and young students (79.9%). Associations were observed between the use of alcohol and stress, with predominance of academic overload. The results provide information relevant to the planning of preventive actions of alcohol use for this population.